Numerical and analytical flow models in ecological channels with interaction of vegetation and freshwater - Zhao, Hanqing; Wang, Weijie; Jia, Fengcong; Wang, Huilin; Liu, Zhiwu; Xu, Yuxuan (Frontiers in Environmental Science, 2023)
Aquatic vegetation interferes with river hydrodynamics, thus affecting the mass transport and energy transfer in an ecosystem. The flow over submerged vegetation is characterized by a complex velocity profile and multiple turbulence structures, which have been usually simulated using cylinders or strips in previous studies. Because the simplified vegetation configuration may hide or amplify some physical processes found in natural conditions, we investigate the velocity distribution and turbulence structure in foliaged vegetation flows using both analytical and numerical approaches. The main innovations and findings can be summarized as follows: (1) numerical and analytical models proposed in this paper accurately simulate the flow velocity in vegetated channel; (2) the Karman constant is found to be unsuitable for complex vegetation morphologies, so we proposed adjusted coefficient; (3) an image processing method is adopted to quantify the vegetation morphology accurately; (4) the existing mixing-layer thickness formula is found to be unsuitable for vegetation with leaves, an improved formula is proposed showing high correlation coefficient (0.9562) between measured and predicted data; (5) to ensure applicability to larger-scale hydrodynamic simulations, an analytical expression of Manning’s coefficient is proposed based on an analytical multi-layer flow velocity model. These research findings can provide theoretical support for the design of vegetated river and ecological restoration.